THE EFFECT OF DISCUSSION METHOD ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Dolli Rotua Sinaga; Kresna Ningsih Manik (STKIP PGRI Jombang, 2021)
This study was intended to find out the effect of using Discussion Method on students reading comprehension. The population of this study was the second semester students of Indonesia Prima University, Medan, academic year 2019/2020 with four parallel classes, there are 120 students totally. The sample of the research was two classes, which were selected by using cluster random sampling technique, the total were 60 students. The sample was divided into two groups; the first group is 30 students, Morning A Class, which was the experimental group. The second group is 30 students, Morning B Class, which was the control group. The experimental group was taught by using discussion method while control group was taught without discussion method. The instrument used for collecting the data was test in the form of multiple choices with the total number of 20 questions. The tests were divided into two; pre-test and post-test. The reliability of the test was 0.93. After the data had been collected, they were analyzed by using t-test formula in order to see whether the discussion method significantly affects students reading comprehension. The result of the analysis showed that the t- observed 2.07, it was higher than the t-table 1, 67 with the level of significant 0, 05 and the degree of freedom (df) 58. The result of the analysis showed that the hypothesis of the study was accepted. It was concluded that discussion method significantly affects students reading comprehension.